The therapeutic community for drug abusers: origin, development, intervention models - Calamo Specchia, Francesco; Scapigliati, Andrea; Terzani, Alessandro (Medicina e Morale, 1990)
In this work authors reviewed different therapeutic approach that are in use in communities for drug abusers in ltaly and abroad, relating to the international first experiences about non obligatory health care. They noticed important differences among various procedures, references, therapeutic goals and finally, points of view about drug related problems.